Influence of Metal Oxide Additives on the Activity and Stability of PtRu/C for Methanol Electro-Oxidation. Issue 7 (1st January 2015) - Sebastián, D.; Stassi, A.; Siracusano, S.; Vecchio, C. Lo; Aricò, A. S.; Baglio, V.
Abstract : Tin, titanium and iridium oxides have been investigated as additives of Pt-Ru based catalysts for the methanol oxidation reaction (MOR). The electro-oxidation of methanol has been studied in a three-electrode configuration for the application of such formulations in direct methanol fuel cell anodes. The presence of the additives produces an increase of catalytic activity, as a consequence of the ability of these metal oxides to form surface oxygen species which react with methanolic intermediates adsorbed on Pt. Among them, iridium oxide presents the highest catalytic enhancement. The stability of this additive has been investigated by potential cycling in 2 M methanol up to 1100 cycles in the interval 0.3–1.0 V vs. RHE. After an initial activation stage, the catalytic activity toward MOR decreases with cycles regardless the presence of the IrO2 additive, indicating no influence of the promoter on Pt-Ru degradation mechanisms. Even if the promoter enhances MOR activity, dissolution of Ru at highly positive potentials causes an irreversible damage which is not compensated by the promoter.